Reporting of D-dimer data in COVID-19: some confusion and potential for misinformation - Favaloro, Emmanuel J; Thachil, Jecko (Clinical chemistry and laboratory medicine, 2020)
Coronavirus disease 2019 (COVID-19) represents a new pandemic caused by severe acute respiratory syndrome virus coronavirus 2 (SARS-CoV-2). A previous pooled analysis clearly identified elevated D-dimer levels as being associated with severity of COVID-19. Since then, several other studies have provided clearer support for this initial evidence. However, potentially under-recognized by those reporting on D-dimer is the considerable variation in reporting units for D-dimer, and thus also the potential for misreporting of D-dimer data based on poor or incomplete reporting. A PubMed search was used to identify recent papers reporting on D-dimers in COVID-19-based studies. We report that: (1) most publications did not identify either the manufacturer or D-dimer product used; (2) most did not identify whether D-dimer values were reported as D-dimer units (DDU) or fibrinogen equivalent units (FEU) (~2 ×  differences); (3) nearly half did not identify normal cut-off values; (4) some did not report numerical findings or units for D-dimer; (5) where reported, most identified units as either mg/L or μg/mL; (6) we identified at least four errors in reporting from 21 papers. It may not be possible to truly standardize D-dimer assays, but it should be feasible to harmonize D-dimer assays to a single unit of measurement.